Molecular Detection of Ehrlichia canis in the Pet-Dog Population in R. N. Macedonia - Petrov, Elena Atanaskova; Celeska, Irena; Popova, Zagorka; Krstevski, Kiril; Djadjovski, Igor; Dzadzovski, Igor (Walter de Gruyter GmbH, 2021)
Abstract Canine monocytic ehrlichiosis (CME) is a widespread, tick-borne, canine disease, caused by an obligate intracellular bacterium, Ehrlichia canis. The main vector, a brown-dog tick, Rhipicephalus sanguineus, is widely distributed, especially in areas with tropic, subtropic, or Mediterranean climates (Central and South America, Eastern and Western Asia, Africa, Australia and Southern Europe). The study performed in 2012, by Stefanovska et al., determined a seroprevalence of 18.7% of E. canis among the Macedonian dog population. Up to date, the presence of E. canis, using molecular diagnostic methods, has not been investigated in Macedonia. Therefore, this study aimed to confirm the presence of E. canis, in the pet-dog population on the territory of the city of Skopje, North Macedonia, using a highly sensitive multiplex Real-Time PCR method (qPCR). Whole blood samples from 80 dogs of different breeds and ages, with clinical symptoms of CME and positive serology result for the presence of antibodies against E.canis, were collected for analyses. Out of 80 dogs, 36 (45%) were found as positive. The present work reports the first molecular detection of E. canis in pet dogs on the territory of the city of Skopje, Macedonia.